An efficient simulation of the fractional chaotic system and its synchronization. Issue 18 (December 2018) - Su, Daliang; Bao, Weimin; Liu, Jie; Gong, Chunye
Abstract: The computational complexity of the numerical simulation of fractional chaotic system and its synchronization control is O ( N 2 ) compared with O ( N ) for integer chaotic system, where N is step number and O is the computational complexity. In this paper, we propose optimizing methods to solve fractional chaotic systems, including equal-weight memory principle, improved equal-weight memory principle, chaotic combination and fractional chaotic precomputing operator. Numerical examples show that the combination of these algorithms can simulate fractional chaotic system and synchronize the fractional master and slave systems accurately. The presented algorithms for simulation and synchronization of fractional chaotic system are up to 1.82 and 1.75 times faster than the original implementation respectively.